2017
DOI: 10.1080/20009666.2017.1347475
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 genetic variation and individualized clopidogrel prescription in a cardiology clinic

Abstract: Background: Clopidogrel (Plavix) is an antiplatelet medication that is routinely used in patients with cardiovascular disease. Cytochrome P2C19 enzymes play a major role in its metabolism, which determines its varied therapeutic level and its effectiveness.Objectives: To customize clopidogrel therapy and evaluate its efficacy by using CYP2C19 genotypic and phenotypic information to improve clinical outcomes in patients.Methods: A total of 465 patients with underlying cardiovascular disease were selected from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…Our study was aimed to find a relationship between patients' genomic profile and their status of polymorphism with reduced scope for aspirin and clopidogrel metabolism. The outcome demonstrated for the presence of 35.9% wild type and 47.2% hetero and 16.9% mutant people who carried CYP2C19*2 variant allele which went in line with the studies conducted in the Malaysian [46], Chinese [47], Egyptian [48] and American [49] healthy population (Table 3) In the case of *17 carriers, a standard or reduced dose of clopidogrel and strict monitoring for potential bleeding of the patient was advised [51]. As stated by the current CPIC guidelines, the following changes are to be made:…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our study was aimed to find a relationship between patients' genomic profile and their status of polymorphism with reduced scope for aspirin and clopidogrel metabolism. The outcome demonstrated for the presence of 35.9% wild type and 47.2% hetero and 16.9% mutant people who carried CYP2C19*2 variant allele which went in line with the studies conducted in the Malaysian [46], Chinese [47], Egyptian [48] and American [49] healthy population (Table 3) In the case of *17 carriers, a standard or reduced dose of clopidogrel and strict monitoring for potential bleeding of the patient was advised [51]. As stated by the current CPIC guidelines, the following changes are to be made:…”
Section: Discussionsupporting
confidence: 73%
“…2. Discontinuing or lowering clopidogrel doses in rapid metabolizer genotype to decrease bleeding risk [51].…”
Section: Discussionmentioning
confidence: 99%
“…In animal subjects, a study proposed that clopidogrel was found to have 3.5-fold associated with higher bleeding risk compared to ticagrelor 48 . Clopidogrel is metabolized by cytochrome P2C19 enzyme 49 , and recent gene-disease interaction studies reported that cytochrome P2C19 CYP2C19*20 C-889T>G (SNP rs11568732) was associated with the risk of bleeding in ACS patients treated with clopidogrel 50 52 . Therefore, theoretically, the risk of major bleeding with clopidogrel should be higher than with ticagrelor.…”
Section: Discussionmentioning
confidence: 99%
“…76 A resposta do indivíduo frente ao clopidogrel pode sofrer alteração, determinada pelo polimorfismo do CYP2C19. 77 A variante de perda de função do CYP2C19*2 foi associada a um risco aumentado de eventos cardiovasculares adversos, incluindo trombose de stent durante o tratamento com clopidogrel. 78 Mais especificamente, o alelo CYP2C19*2 (rs4244285) causa perda de função e foi associado à redução na atividade antiagregante do medicamento.…”
Section: Clopidogrelunclassified